2008
DOI: 10.1080/03014460802014625
|View full text |Cite
|
Sign up to set email alerts
|

Discordance of international adiposity classifications in Australian boys and girls – The LOOK study

Abstract: In contrast to the BMI-based charts, there were considerable variations in depicted incidences of obesity between the %BF-based charts. These discordances were considered to result from previously reported variation within and between BIA and DXA %BF assessments underlying the charts. The present study highlights the need for valid, reliable, unchanging BIA and DXA procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…show unadjusted characteristics of the participants at each testing phase. To permit a general weight status comparison with other populations, and acknowledging the limitations of body mass index (BMI) as a surrogate for %BF in our cohort (Telford et al., ), BMI‐based classifications (Cole et al., ) in grade 2 identified 24% and 20% of boys and girls, respectively, as overweight or obese.…”
Section: Resultsmentioning
confidence: 99%
“…show unadjusted characteristics of the participants at each testing phase. To permit a general weight status comparison with other populations, and acknowledging the limitations of body mass index (BMI) as a surrogate for %BF in our cohort (Telford et al., ), BMI‐based classifications (Cole et al., ) in grade 2 identified 24% and 20% of boys and girls, respectively, as overweight or obese.…”
Section: Resultsmentioning
confidence: 99%
“…Precision of measurement has been suggested as a factor that may reduce the accuracy of calculated relationships (21), but while DXA may lack validity it does not lack reliability (22); so measurement of %BF was unlikely to have been a confounding issue in our longitudinal analyses. In any case, significant relationships between IR and %BF were observed in cross‐sectional analyses.…”
Section: Discussionmentioning
confidence: 97%
“…A further 27 potentially eligible studies were identified from the database searches and enquiry e-mails were sent to the authors. Of these, eight generously agreed to provide raw data, [18][19][20][21][22][23][24][25] one of whom provided raw data for three additional, as yet unpublished, cohorts. 20 The authors of a further study, in addition to published data, agreed to provide more recent, as yet unpublished, summary data.…”
Section: Discussionmentioning
confidence: 99%
“…Of these, eight generously agreed to provide raw data, [18][19][20][21][22][23][24][25] one of whom provided raw data for three additional, as yet unpublished, cohorts. 20 The authors of a further study, in addition to published data, agreed to provide more recent, as yet unpublished, summary data. 26 As well, summary data were available from two papers identified in the database search 27,28 (Figure 1).…”
Section: Discussionmentioning
confidence: 99%